Dehydration as a strategy for rapid weight loss in Fighters (Research, Society and Development, 2023)
M.M.A (Mixed Martial Arts) is a combat sport that encompasses the most varied types of fighting, in which competitors are divided into categories according to their weight. Therefore, many fighters seek strategies, such as dehydration, to adapt to lower categories. The objective of the work is to evaluate the behaviors used for dehydration and the impacts of this practice on the athlete’s sporting performance in the pre- and post-competitive period. The study is a bibliographic review with articles related to the topic, with the aim of clarifying the harmful effects on health of rapid weight loss without adequate nutritional monitoring. Analysis of the results showed that some athletes experienced cramps, severe headaches, decreased performance and significant hormonal changes as a result of the practice. Given the results, the need for more in-depth studies on the topic and its main consequences is notable.